2002
DOI: 10.1016/s0043-1648(02)00234-x
|View full text |Cite
|
Sign up to set email alerts
|

Rolling contact fatigue of surface coatings—a review

Abstract: The aim of this review is to survey the state of the art relating to the rolling contact fatigue (RCF) investigation of various overlay coatings and also, to ascertain the influence of design parameters such as the type of deposition process, coating material and thickness on the RCF performance. Rolling contact fatigue is a significant factor in the failure of components in rolling/sliding contact. Although, sintered ceramics have provided improvements in RCF life of components in rolling/sliding contact, e.g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(61 citation statements)
references
References 37 publications
(47 reference statements)
1
47
0
1
Order By: Relevance
“…A number of previous review articles have been presented on different forms of CVD: thermal CVD [2][3][4][5][6][7][8][9][10][11], plasma enhanced PE-CVD [12][13][14][15][16][17][18][19], hot-wire or hot filament (HWCVD or HFCVD) [20][21][22][23][24][25][26][27][28] and not many of them have been as exhaustive in their respective areas. Pyrolysis, although classified under CVD in some text, has become a wide area of research and technology covering synthesis of new products, qualitative and quantitative spectroscopic analysis of fluids and, lately, alternative route to production of debri-free x-ray sources; these aspects are elaborated further in the sections that follow.…”
Section: Fig 1 Generalised Schematic Of Chemical Vapor Deposition Symentioning
confidence: 99%
“…A number of previous review articles have been presented on different forms of CVD: thermal CVD [2][3][4][5][6][7][8][9][10][11], plasma enhanced PE-CVD [12][13][14][15][16][17][18][19], hot-wire or hot filament (HWCVD or HFCVD) [20][21][22][23][24][25][26][27][28] and not many of them have been as exhaustive in their respective areas. Pyrolysis, although classified under CVD in some text, has become a wide area of research and technology covering synthesis of new products, qualitative and quantitative spectroscopic analysis of fluids and, lately, alternative route to production of debri-free x-ray sources; these aspects are elaborated further in the sections that follow.…”
Section: Fig 1 Generalised Schematic Of Chemical Vapor Deposition Symentioning
confidence: 99%
“…It has been shown that hard coatings and other surface modification methods are able to improve the resistance of rolling elements (i.e., bearings) to friction, wear and corrosion [2,3]. Thin diamond-like-carbon (DLC) coatings, for instance, provide protective, low friction, wear resistant surfaces for numerous industrial applications such as invasive and implantable medical devices, razor blades, magnetic hard discs and microelectromechanical systems [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of these coatings are used to improve the resistance of cutting tools [1][2], but also other engineering equipment, which use good resistance of these coatings e.g. to classical or contact fatigue [3][4]. TiCN coating has been known for several decades, and during that time numerous papers were published dealing with such coating and its properties.…”
Section: Introductionmentioning
confidence: 99%